Prevalence, Risk Factors and Comorbidities of Allergic Rhinitis in South Korea: The Fifth Korea National Health and Nutrition Examination Survey. Issue 2 (March 2014) - Rhee, Chae-Seo; Wee, Jee Hye; Ahn, Jae-Cheul; Lee, Woo Hyun; Tan, Keng Lu; Ahn, Soyeon; Lee, Ju Hyun; Lee, Chul-Hee; Cho, Yang-Sun; Park, Kyoung Ho; Lee, Kun Hee; Kim, Kyung-Su; et al.
Background: There has been no nationwide epidemiological investigation of allergic rhinitis (AR) that was diagnosed by both questionnaires and laboratory tests in Korea. This study investigated the prevalence, risk factors, and comorbidities of AR in South Korea. Methods: The Korean National Health and Nutritional Examination Survey examined a representative sample of the Korean population. A total of 2305 participants underwent immunoradiometric assay for specific IgE antibodies against common indoor allergens. Healthy, atopy only, and AR groups were defined according to the results of allergen test. The weighted prevalence for each group was calculated. Risk factors including food and comorbidities were identified using univariate or multivariate analyses. The patients were also categorized into four subgroups according to the Allergic Rhinitis and Its Impact on Asthma (ARIA) classification and associated comorbidities were analyzed. Results: The prevalence of atopy only and AR was 30.0 ± 1.2% and 16.2 ± 1.0%, respectively. The multivariate analysis showed that the prevalence was influenced by sex (p < 0.01) for atopy only and sex (p = 0.09), age (p = 0.02), marital status (p = 0.24), and stress level (p = 0 for AR. Compared with the healthy group, asthma (odds ratio [OR] = 4.77), nasal polyp (NP; OR = 3.44), chronic rhinosinusitis (OR = 13.93), and olfactory dysfunction (OR = 4.88) were more prevalent in the AR group. Based on the ARIA guideline, intermittent mild rhinitis was most common (58.1%). Asthma was correlated to severity and atopic dermatitis and NPs was associated with persistency. Daily intake of less mackerel and more carrots, bread, and bean curd were associated with the increased risk of AR. Conclusion: Prevalence, risk factors, and comorbidities of AR were evaluated in the general Korean population, which will contribute to prevention and treatment of AR and its comorbidities in Koreans.